Studying the Behavior of a Paperboard Box: Experiment and Finite Element Model - Boussad Abbès; Fazilay Abbès; Lien Tien Dao; Pham Tuong Minh Duong; Viet Dung Luong (Vibration, 2025)
In the transportation and distribution of goods, cardboard boxes are often subjected to mechanical impacts such as shocks and random vibrations, which can cause damage to the goods. In this study, static and dynamic tests on cardboard boxes were designed and conducted to determine the compression strength, natural frequencies, and modal characteristics of the boxes. A finite element model of cardboard boxes considering the in-plane orthotropic elastic–plastic behavior of the cardboard was implemented in the Abaqus software through a VUMAT subroutine to perform numerical simulations under compression and random vibrations. The parameters of the model were determined through an inverse identification process. As a first result, the predicted force–displacement curves show good agreement with the measured curves. Furthermore, the power spectral density (PSD) response of the mass/box system under random vibrations obtained through numerical simulations is consistent with the responses obtained from experimental measurements.